How do you solve 4( 2- 5x ) = 6- 3( 1- 3x )?

2 Answers
Jul 28, 2018

x=5/29

Explanation:

4(2-5x)=6-3(1-3x)

Expand the brackets
8-20x=6-(3-9x)

8-20x=6-3+9x

Simplify
8-20x=3+9x

Move the x onto one side
29x=5

Divide both sides by 29
x=5/29

Jul 28, 2018

x=5/29

Explanation:

We can distribute the 4 on the left side, and the -3 on the right. Doing this, we now have

8-20x=6-3+9x

We can combine like terms to get

8-20x=3+9x

Let's get our constants on one side by subtracting 8 from both sides:

-20x=-5+9x

Next, subtract 9x from both sides to get

-29x=-5

Lastly, we can divide both sides by -29 to get

x=5/29

Hope this helps!